An Exploration of the Relationship between PBIS and Discipline Outcomes for Students With Disabilities. (October 2022) - Simonsen, Brandi; Freeman, Jennifer; Gambino, Anthony J.; Sears, Sandra; Meyer, Katherine; Hoselton, Robert
To support all students, including students with disabilities, many schools have adopted a positive behavioral interventions and supports (PBIS) framework. Although rigorous research documents the beneficial effects of Tier 1 PBIS for all students and emerging research extends these findings to students with disabilities, there has not been a national U.S. study focused on PBIS and discipline outcomes for students with disabilities. In this exploratory study, we combine existing national data sets to explore the relationship between (a) known PBIS exposure (i.e., being in the PBIS data set) and fidelity (i.e., meeting the criterion on an established fidelity measure of Tier 1 PBIS) and (b) exclusionary discipline for students with disabilities. Using two-part path analysis, we document that PBIS may be associated with decreased use of suspension; however, findings are less consistent for other discipline outcomes. This study highlights the critical need for more accurate data on discipline outcomes and further research on effective intervention.